2019
DOI: 10.1039/c8ra09161g
|View full text |Cite|
|
Sign up to set email alerts
|

Non-thermal plasma assisted surface nano-textured carboxymethyl guar gum/chitosan hydrogels for biomedical applications

Abstract: Surface nano-textured carboxymethyl guar gum/chitosan smart hydrogels by non-thermal plasma for biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The well-growth of cells for PEG 10k -5PEG 150 -8S is comparable to that of the control group, which intuitively demonstrates excellent cytocompatibility of the hydrogel. In addition, the hemolysis ratios of the precursor and the extract of the PEG 10k -5PEG 150 -8S hydrogel are 1.8% and 0.1%, respectively (Figure S22), much lower than the critical hemolysis ratio of 5% for the safe use of biomaterials . Overall, it can be concluded that our full PEG hydrogels exhibit an excellent biocompatibility, which possess a promising application prospect in biomedical fields.…”
Section: Results and Discussionmentioning
confidence: 87%
“…The well-growth of cells for PEG 10k -5PEG 150 -8S is comparable to that of the control group, which intuitively demonstrates excellent cytocompatibility of the hydrogel. In addition, the hemolysis ratios of the precursor and the extract of the PEG 10k -5PEG 150 -8S hydrogel are 1.8% and 0.1%, respectively (Figure S22), much lower than the critical hemolysis ratio of 5% for the safe use of biomaterials . Overall, it can be concluded that our full PEG hydrogels exhibit an excellent biocompatibility, which possess a promising application prospect in biomedical fields.…”
Section: Results and Discussionmentioning
confidence: 87%
“…This behavior was also reported for Na5 1 * hydrogels and it can be related to the difference in osmotic pressure between the hydrogel’s structure and the saline solutions [ 24 ]. Furthermore, the neutral pH of the PBS solution (7.4) might induce an increase in the swelling ratio of hydrogels due to the deprotonation of -NH 3 and the intra-chain hydrogen bonds in the hydrogel matrix [ 42 ]. Nonetheless, the slight difference between the swelling ratio in PBS and NaCl 0.9% suggested the absence of a pH-sensitive swelling behavior.…”
Section: Resultsmentioning
confidence: 99%
“…These differences between GG beads and CMGG beads, in terms of porosities and ceramic distribution in the organic part, are explained by the results of a study published by Dalei et al [ 15 ], where GG micrographs revealed a discrete and elongated structure with particles separated from each other, while CMGG micrographs showed a substantially altered morphology, with particles adhering to each other and forming larger aggregates, more evidence of an increased CMGG concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its glycopolysaccharide structure, GG, isolated from ground endosperm of Cyamopsis tetragonolobus or Cyamopsis psoraloides, interacts and binds with proteins in a physiological environment [ 13 ]. Carboxymethyl GG (CMGG) expresses increased hydrophilicity and clarity solution [ 14 ] and can be designed as nanoparticles and microspheres to hydrogels for various biomedical applications [ 15 ].…”
Section: Introductionmentioning
confidence: 99%